A prospective open label randomized controlled trial comparing the effect of letrozole and mifepristone pre-treatment in medical termination of pregnancy up to 9 weeks - Jogi, Sangeeta Raman; Singh, Dipika; Garhewal, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Mifepristone for medical termination of pregnancy (MTP) has been shown to increase the success rate. mifepristone followed by misoprostol for the medical management of first trimester pregnancy in previous clinical trials has ranged from 79% to 87%. As access to mifepristone is restricted in some countries, and some patients may have contraindications to the use of mifepristone, we propose that letrozole may be a good alternative. Methods: This was a hospital based open label randomized controlled trial study carried out year 2023 to 2024 in the department of obstetrics and gynecology at CIMS Bilaspur, total sample was 100. Results: In present study both groups received a single dose of their respective drug, with a slightly higher proportion of mifepristone users receiving two doses (14%) compared to letrozole users (6%) and in gestational sac expulsion 84% of participants from both groups expelled the sac in 2 days, mifepristone users had a slightly higher rate of incomplete expulsion (6%) compared to letrozole users (4%) (p=0.041). Conclusions: The comparison between letrozole and mifepristone users highlights several key differences. Mifepristone users experienced a higher frequency of irregular menstrual cycles, incomplete expulsion of the gestational sac, and a greater need for dilation and curettage (D and C) procedures compared to those using letrozole.